MITIGATING THE ELECTROMAGNETIC VULNERABILITY OF RESTRICTED INFORMATION - Tarasenko, Yu. S. (Systems and Technologies, 2023)
The article presents a review of research on decision-making from the perspective of risk-information security of a set of critical infrastructure facilities. At present, characterized by the inevitability of the coming hot phases of information wars, security aspects manifest themselves in all spheres of society: from domestic to scientific and industrial, where the security of the state, society and the individual is considered dominant. In this context, the importance of assessing the security of any modern facilities, primarily critical facilities with their information infrastructures, ensuring the completeness and reliability of the information in the involved computer networks with computer facilities, is always relevant and necessary, Threats to information resources should be seen as potentially possible cases of man-made, man-made or natural (natural) nature, which may cause undesirable effects on the information and telecommunications industry. The analysis of potential sources of electromagnetic vulnerability of information, processed by computer facilities, is performed. Potential variants of information leakage due to undesirable electromagnetic influence (radiation and pickups) of parasitic electromagnetic emission and pickups type are detailed. Perspective protective actions on leveling such influences in the form of creation of a mode of anechoic stability and additional shielding which provide minimization of negative consequences on reliability, integrity and confidentiality of the information, processed by means of computer techniques are considered. The technology of a parasitic radiation assessment outside the controlled area of the object by computer aids is offered both for mobile (by means of drones) its realization and for stationary variants of control and measuring apparatus usage with automatic indication of alarm signal about exceeding of acceptable level of a parasitic electromagnetic radiation leakage. In the part relating to information leakage through technica channels of the object of informatization, it is possible to considerably level the electromagnetic vulnerability of service information, occurring during operation of computer facilities, by implementing appropriate countermeasures against insufficient shielding, incidental electromagnetic radiation and induction, and unauthorized use in computer facilities of high-frequency irradiation.